Ahmaud Arbery: murder as the outcome of an assemblage's enactment. (2nd November 2021) - Vila, Pablo; Ford, Matt; Avery-Natale, Edward
ABSTRACT: On February 23rd, 2020, Ahmaud Arbery, a Black man out for a jog in Georgia, was murdered by two white men who, acting as vigilantes, assumed Arbery was responsible for recent burglaries. While Blacks being murdered by whites in America is nothing new, new theories of identification – specifically, assemblage theory and identitarian articulations – offer us tools to better understand how such events take place. Specifically, we argue that racialization occurs not just on the body, but through a complex process resulting in 'race' immanently emerging as the outcome of an assemblage. In this article, we show, first, that Arbery, through no fault of his own, entered into a 'Neighborhood Watch Assemblage' that already anticipated the body of a Black man that would fulfill an overdetermined role as 'criminal' and that this identitarian articulation emerges through the arrangement of several identifications, bodies, technologies, objects, discourses, affects, and emotions that, together, actualize 'races' on bodies. Tragically, in this case, death became a capacity of the assemblage. In contrast to the death of an innocent man in Georgia, we secondly analyze what occurred in Kenosha, Wisconsin, where a 'Law and Order' assemblage's outcome resulted in a White identitarian articulation not being, initially, interpellated as 'criminal' even though the person had committed murder. Overall, we show that assemblage theory and the concept of identitarian articulations help us better understand such occurrences. Such analyses can shed a different light on episodes of systemic racism and can, eventually, help in overcoming it.